Remittances and financial development in Africa - Ibrahim A. Adekunle; Sheriffdeen A. Tella; Kolawole Subair; Soliu B. Adegboyega (African Governance and Development Institute (AGDI), 2020)
Despite the magnitude of remittances as an alternative source of investment financing in Africa, the financial sector in Africa has significantly remained underdeveloped and unstable. Finding a solution to Africa's financial deregulation problems has proved tenacious partly because of inadequate literature that explain the nature of Africa capital and financial markets which has shown to be unorganised, spatially fragmented, highly segmented and invariably externally dependent. We examine the structural linkages between remittances and financial sector development in Africa. Panel data on indices of remittances was regressed on indices of financial sector development in fifty-three (53) African countries from 1986 through 2017 using the Pooled Mean Group (PMG) estimation procedure. We accounted for cross-sectional dependence inherent in ordinary panel estimation and found a basis for the strict orthogonal relationship among the variables. Findings revealed a positive long-run relationship between remittances and financial development with a significant (positive) short-run relationship. It is suggested that, while attracting migrants' transfers which can have significant short-run poverty-alleviating advantages, in the long run, it might be more beneficial for African governments to foster financial sector development using alternative financial development strategies.
Keywords: F37; G21; O16; 330; Remittance; Financial Development; Pooled Mean Group; Africa